Awareness about Diabetes Mellitus Amongst Diabetics - Tahir Iqbal , Farah Rashid , Salman Ahmad Saleem , Shoaib Ahmad Shah , Ghulam Haider Khalid , Osama Ishtiaq (Journal of Rawalpindi Medical College, 2013)
Background: To compare the level of awareness of diabetes mellitus, in diabetic patients visiting two different tertiary care heath facilities . Methods: In this cross-sectional study diabetic patients suffering from either type 2 or type 1 diabetes mellitus, between the ages of 16-80 years were included. Demographic data and knowledge of participants was recorded about various aspects of diabetes mellitus. T-test was applied to find out the difference of knowledge about diabetes between urban and rural population. Results: Out of total of 246 patients, ranging from 16-80 years(54.50+10.89),59.3% were females. A significant proportion of study participants (32%) attributed excessive intake of sweets for the causes of diabetes. Role of physical activity and exercise was acknowledged by 44.3% patients. Low cholesterol diet was reported to be protective for heart by 15.9%. Urban patients were more well versed with complications of diabetes mellitus. Conclusion: The awareness about diabetes mellitus in majority of diabetic patients was inadequate. Urban population has better understanding of the disease as compared to rural population.